2016
DOI: 10.1186/s13223-016-0139-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of adverse food reactions in Portuguese adults

Abstract: BackgroundOnly one previous study, via telephone call, on the prevalence of self-reported food allergies has been performed in Portugal, in a small sample of adults. The objective of this study was to determine the prevalence of self-reported and probable food allergy, analyze the clinical features and involved foods in Portuguese adults.MethodsPopulation-based, cross-sectional study performed in various healthcare centres from central Portugal. All 1436 randomly selected individuals (median age: 45 years, 50.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
2
10
0
2
Order By: Relevance
“…Our results are different from those more frequently reported in children in other countries, in which the most prevalent foods have been cow’s milk, peanut, eggs, or wheat [ 18 , 24 , 28 ] although a German study in children and adolescents also found fruits as the most frequently reported and confirmed cause of food-induced symptoms [ 19 ]. Previous Portuguese reports also showed a high relevance of fresh fruits in AFR in adults [ 10 , 29 ] and in children with an age range similar to that in our study [ 11 ], and similar results were observed in Spanish children [ 30 ]. Since the diet followed by children in our study is similar to that in other regions of Portugal, the high prevalence of probable allergy to fresh fruits and fish may be due to the mediterranean type of diet of the population.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are different from those more frequently reported in children in other countries, in which the most prevalent foods have been cow’s milk, peanut, eggs, or wheat [ 18 , 24 , 28 ] although a German study in children and adolescents also found fruits as the most frequently reported and confirmed cause of food-induced symptoms [ 19 ]. Previous Portuguese reports also showed a high relevance of fresh fruits in AFR in adults [ 10 , 29 ] and in children with an age range similar to that in our study [ 11 ], and similar results were observed in Spanish children [ 30 ]. Since the diet followed by children in our study is similar to that in other regions of Portugal, the high prevalence of probable allergy to fresh fruits and fish may be due to the mediterranean type of diet of the population.…”
Section: Discussionsupporting
confidence: 92%
“…As previously reported by studies of food allergy prevalence in European countries, in our patients the types of foods most frequently implicated are included in the so-called "big eight allergens": milk, egg, peanut, tree nuts, wheat, soy, fish and shellfish (4). However, and as Lozoya-Ibáñez et al reported in their work about self-reported food allergy, the individual prevalence of each food type is distinct, which may be due to cultural differences in food habits.…”
Section: Cofactors and Anaphylaxismentioning
confidence: 91%
“…In the last decades, the prevalence of food allergies has increased in several regions throughout the world (3). Although food allergy is not as prevalent as other allergic diseases, its repercussions on dietary habits and social interaction is quite relevant (4). Allergic reactions to foods are the leading cause of anaphylaxis in patients of all ages outside the hospital setting (5); however, the precise risk of anaphylaxis is unknown (2).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, a multi-center survey reported 4.8% of adults to have IgE sensitization to shrimp as compared to hazelnut (9.3%), peach (7.9%) and apple (6.5%) [15]. Shellfish was the leading food allergen in Portugal, affecting 34.6% of all food-allergic patients and 2.1% of the entire study population of 840 adults [16]. Most children from the Isle of Wight birth cohort reported shellfish allergy during adolescence, by which none of these subjects had IgE sensitization to shellfish at 1, 2, and 4 years while 0.2% of the subjects developed shellfish allergy at 10 and 18 years [17].…”
Section: Epidemiologymentioning
confidence: 99%